Odpowiedzi

  • Użytkownik Zadane
2010-03-04T17:19:12+01:00
A) 4x-3=3x+5
x=8
b)5x+2=7-3x
8x=5
x=5/8
c)3(x-1)=0
3x=3
x=1
d)-6(x+1)=24
-6x=30
x=-5
e)-7(x-2)=3x-1
-7x-3x=14-1
-10x=13
x=-13/10
f)4(x-1)=6(1+x)
4x-6x=4+6
-2x=10
x=-5
2010-03-04T17:23:48+01:00
A) 4x-3=3x+5
4x-3x=5+3
1x=8 x=8
b) 5x+2=7-3x
5x+3x=7-2
8x=5 /:8
x=5/8
c) 3(x-1)=0
3x-3=0
3x=3 /:3
x=1
d) -6(x+1)=24
-6x-6=24
-6x=24+6
-6x=30 /:-6
x=-5
e) -7(x-2)=3x-1
-7x+14=3x-1
-7x-3x=-1-14
-10x=-15 /:-10
x=1,5
f) 4(x-1)=6(1+x)
4x-4=6+6x
4x-6x=6+4
-2x=10 /:-2
x=-5
/ oznacza dzielenie obustronne